Emotional intelligence and compliance with the school management commitments of the initial education management staff - Núñez-Rojas, Flor de María I. (2019)
The aim of the research work was to demonstrate how emotional intelligence is related to school management commitments in the management staff of the Initial Level, Network 1, UGEL Ventanilla Callao, 2018. The methodology used was descriptive correlational. For the collection of data, two instruments were elaborated. For the first variable, a sample of 13 educational institutions of the initial level of the network 01, 66 teachers, 13 managers and 13 administrative personnel, for the second variable a checklist was used through documentary analysis. The results indicated that emotional intelligence is significantly related to school management commitments, so it is concluded that the correlation is significant and reaches a level of 0.821 that corresponds to a high positive correlation level.